Respuesta :

Hi,

This is the same situation as a sequence case.

You have two informations :

[tex]\left \{ {{f(1)=5} \atop {f(n)=4f(n-1)-2}} \right.[/tex]

You need to solve this rank by rank for n = 1, 2, 3, 4 and 5.

We already have f(n) for n = 1 : it is f(1) = 5.

n = 2 :

f(2) = 4 * f(2-1) - 2 = 4 * f(1) - 2 = 4 * 5 - 2 = 20 - 2 = 18 because f(1) = 5

n=3 :

f(3) = 4 * f(3-1) -2 = 4 * f(2) -2 = 4 * 18 -2 = 72 - 2 = 70

n = 4 :

f(4) = 4 * f(4-1) -2 = 4* f(3) - 2 = 4* 70 - 2 = 280 - 2 = 278

n = 5 :

f(5) = 4 * f(5-1) - 2 = 4*f(4) - 2 = 4 * 278 - 2 = 1112 - 2 = 1110

so f(5) = 1110

Good Luck